Blockade of muscarinic receptors impairs the retrieval of well-trained memory - Soma, Shogo; Suematsu, Naofumi; Shimegi, Satoshi (Frontiers in Aging Neuroscience, 2014)
Acetylcholine (ACh) is known to play an important role in memory functions, and its deficit has been proposed to cause the cognitive decline associated with advanced age and Alzheimer’s disease (the cholinergic hypothesis). Although many studies have tested the cholinergic hypothesis for recently acquired memory, only a few have investigated the role of ACh in the retrieval process of well-trained cognitive memory, which describes the memory established from repetition and daily routine. To examine this point, we trained rats to perform a two-alternative forced-choice visual detection task. Each trial was started by having the rats pull upward a central-lever, which triggered the presentation of a visual stimulus to the right or left side of the display monitor, and then pulling upward a stimulus-relevant choice-lever located on both sides. Rats learned the task within 10 days, and the task training was continued for a month. Task performance was measured with or without systemic administration of a muscarinic ACh receptor (mAChR) antagonist, scopolamine (SCOP), prior to the test. After 30 min of SCOP administration, rats stopped manipulating any lever even though they explored the lever and surrounding environment, suggesting a loss of the task-related associative memory. Three hours later, rats were recovered to complete the trial, but the rats selected the levers irrespective of the visual stimulus, suggesting they remembered a series of lever-manipulations in association with a reward, but not association between the reward and visual stimulation. Furthermore, an m1-AChR, but not nicotinic AChR antagonist caused a similar deficit in the task execution. SCOP neither interfered with locomotor activity nor drinking behavior, while it influenced anxiety. These results suggest that the activation of mAChRs at basal ACh levels is essential for the recall of well-trained cognitive memory.